IRON AND CALCIUM UPTAKE BY RICE PLANTS CULTIVATED IN NUTRITIONAL SOLUTION WITH MANGANESE AND SILICON DOSES - ZANÃO JÚNIOR, Luiz Antônio; FONTES, Renildes Lúcio Ferreira; ÁVILA, Vinícius Tavares de; KORNDÖRFER, Gaspar Henrique (Scientia Agraria, 2010)
The concentrations and contents of Fe and Ca in the plant were evaluated in rice plants grown in nutritional solution with increasing Mn doses, with or without Si. The treatments were arranged in a 2x3 factorial (0 or 2 mmol dm-3 Si; 0.5; 2.5 and 10 µmol dm-3 Mn), in a completely random design with four replications. The experimental unit was a 4 dm³ pot with six rice plants, cv. Metica-1. Thirty nine days after plant growth in the the solutions with the treatments it was determined the concentrations and contents of Fe and Ca in root and leaf blade (leaf). The bigger Mn dose decreased the Fe and Ca uptake. The addition of Si to the nutritional solution caused the decrease of Fe translocation from roots to shoots.